Hydrodynamic Condition Modeling along the North-Central Coast of Vietnam - Cham, D. D.; Son, N. T.; Minh, N. Q.; Hung, N. T.; Tien Thanh, N. (Engineering, Technology & Applied Science Research, 2020)
An extremely dynamic morphology of the estuary is observed in the coastal regions of Vietnam under the governing processes of tides, waves, and river system flows. The primary target of this paper is to provide insight into the governing processes and morphological behavior of the NhatLe estuary, located in the north-central coast of Vietnam. Based on measured data from field surveys and satellite images combined with numerical model simulations of MIKE and Delft3D, the influences of seasonal river flow, tides, and wave dynamics on the sediment transport and morphological changes are fully examined. The study showed that freshwater flow in the flood season plays a central role in cutting off the southern sandspit, maintain and shaping the main channel. The prevailing waves in winter and summer induce longshore drift and sediment transport in the southeast to northwest direction. In the low flow season, this longshore sediment transport is dominant, causing sediment to deposit on the southern side of the ebb tidal delta and elongating the southern sandspit which narrows the estuary entrance and reorients the main channel.